Analisis Akuntansi Zakat Perniagaan di Kota Medan - Harahap, Taufiq Azmi (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2023)
This study aims to determine the practice of commercial zakat accounting in the city of Medan. This study uses a qualitative descriptive method by using a phenomenological study approach in which the purpose of this study is to reveal facts, circumstances, phenomena, variables, and circumstances that occurred during the research and state what it is. The results show that first, the level of knowledge and practice carried out by traders about commercial zakat in Medan City is still minimal or low. Second, the lack of knowledge and practice of commercial substances in Medan City. Third, the difference in the trading zakat calculation system is carried out. Fourth, the calculation of trade zakat carried out by 98% of modern Traditional Market traders in Medan City is not in accordance with Islamic law because 23% of traders do not calculate debt, receivables and capital, 33% do not calculate receivables and 42% do not calculate capital and only 2% of traders which calculates according to the guidance of Islamic law because it calculates profits, receivables, capital, and debts